The Effect of Wall Shooting Exercise Using the Beef Concept on Free Throw Shooting Accuracy in High School Women Students - Enna Angela M (Inspiree)
The  purpose  of  the study. This research was motivated by the results of the free throw performed by the women's basketball extracurricular which was not optimal and not appropriate in its implementation. free throw is the accuracy of the direction of the ball shot towards the ring, where this shot is taken from behind the free throw line in a basketball game.